Implementation Analysis of a Temperature and Humidity Control System For a Nodemcu-Based Smart Food Storage Box - Dina Tampubolon; Solly Aryza; Ahmad Dani (INFOKUM, 2025)
An optimal food storage system is essential to maintain quality and prevent spoilage due to changes in temperature and humidity. This study aims to analyze the implementation of a temperature and humidity control system in a smart food storage box based on Arduino and NodeMCU. This system uses a DHT22 sensor to detect temperature and humidity in real-time, a Peltier module as a cooler, and a fan and heater to control air conditions in the box. Arduino Uno is used as the main controller, while NodeMCU ESP8266 plays a role in data communication to the IoT platform for remote monitoring. The methods used in this study include hardware and software design, temperature and humidity stability testing, and system efficiency analysis in maintaining optimal food storage conditions. The test results show that the system is able to maintain temperatures in the range of 5–15°C with a deviation of ±1°C and humidity in the range of 50–70% RH, depending on the type of food stored. In addition, IoT integration allows real-time data monitoring through a cloud-based application. The conclusion of this study shows that the developed Smart Food Box system can operate effectively in maintaining food quality. The use of IoT technology increases the ease of remote monitoring and control, so this system has the potential to be applied on a household and industrial scale.